Effect of Physical Training on Oxygen Saturation at Very High Altitude in Young Males - Raza, Syed Hassan; Satti, Shahzeb Ahmed; Arshad, Abdur Rehaman; Chaudry, Azhar Ali; Imran, Muhammad; Iftikhar, Raheel (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the effect of physical training on oxygen saturation at very high altitude in young male individuals.Study Design:  Prospective longitudinal study.Place and Duration of Study: Department of Pulmonology PEMH Rawalpindi from Jun–Jul 2022.Methodology: The study was done on 250 young individuals arriving at a height of 11,820 feet for the very first time. All individuals were made to stay at the same height for the study period of 28 days. Individuals were tasked to walk 100 meters daily at a steady pace to ensure physical activity. Oxygen saturation was measured, before and after walking 100 meters at a height of 11,820 feet on day 0, day 7, day 14 and day 28 respectively.Results: Mean age of the study participants was 28.08±4.82 years. On day 0, post walk average oxygen saturation was 91.53±1.80%. After a stay of 28 days at a height of 11, 820 feet post walk average oxygen saturation increased to 92.24±2.18%.  Conclusion: The oxygen saturation of young individuals improved over a period of 28 days stay after physical training. Human body adapts to physical training at high altitude by undergoing a large number of physiological processes resulting in improved exercising capacity and increase in oxygen saturation over a period of time.